#TITLE_ALTERNATIVE# - PURNAMA (NIM 23206330), BEDY
One of many models that is used to understand physical process is water model. Not as simple as it seems, water modeling is relatively difficult to do because of the complexity in representing its fluid behaviors such as convection, diffusion, turbulence and surface tension. The smoothed particle hydrodynamic (SPH) method is an interpolation of particle systems using mesh-less Lagrangian. In SPH, field quantities are merely defined at discrete particle locations that can be evaluated anywhere in space. SPH quantity distribution in each particle is influenced by its neighborhood particles in local domain. Smoothing kernel radial symetry is used to compute that SPH quantity distribution. In SPH method, the fluid model of tsunami is determined by gravitation force, viscosity force, surface tension force and pressure force parameters. Having this, a more realistic fluid simulation is obtained. The fluid model of tsunami needs external controlled forces that propagate to the coast. The model uses coast heightmap data of West Aceh that hit by tsunami in 2004. Evaluation is done by comparing the water maximum height obtained from the simulation of two models, i.e. the fluid model of tsunami and TUNAMI-N3. The results obtained from the use of the fluid model of tsunami using SPH show that the water maximum height is more realistic.